2014
DOI: 10.1111/hae.12449
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factorIX: discrepancies between one‐stage clotting and chromogenic assays

Abstract: New and modified recombinant factor IX (rFIX) products are in development and accurate potency estimation is important to ensure the consistency of production and efficacy of these therapeutics. Collaborative study data obtained during the replacement of the 3rd International Standard (IS) for FIX concentrate suggested that there was a discrepancy between potency estimates for rFIX using clotting and chromogenic methods, when the rFIX candidate was measured against the plasma-derived FIX (pdFIX) IS. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 20 publications
3
57
0
Order By: Relevance
“…Recoveries of two rFIX products (Benefix ® and Rixubis ® ) and the EHL product (Alprolix ® ) demonstrated that CSAs generally give closer and more consistent agreement to target levels compared to any of the three OSA protocols employed, where two of three APTT reagents tended to over‐recovery for Benefix ® and Rixubis ® (Figure ). This pattern of similar recovery of pdFIX and discrepant recovery of rFIX products using plasma calibration standards between OSA and CSA by Hyphen test has been previously reported . Consistent with the present study, in a collaborative study assessing postinfusion FIX assays, median CSA results were around 25% lower than median OSA results ( P < .01) with Benefix ® .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recoveries of two rFIX products (Benefix ® and Rixubis ® ) and the EHL product (Alprolix ® ) demonstrated that CSAs generally give closer and more consistent agreement to target levels compared to any of the three OSA protocols employed, where two of three APTT reagents tended to over‐recovery for Benefix ® and Rixubis ® (Figure ). This pattern of similar recovery of pdFIX and discrepant recovery of rFIX products using plasma calibration standards between OSA and CSA by Hyphen test has been previously reported . Consistent with the present study, in a collaborative study assessing postinfusion FIX assays, median CSA results were around 25% lower than median OSA results ( P < .01) with Benefix ® .…”
Section: Discussionsupporting
confidence: 91%
“…Barrowcliffe reported that a chromogenic assay under‐estimated potency of recombinant FIX (rFIX) relative to OSA. More recent studies have shown FIX estimates for rFIX to be significantly lower by CSA than for OSA, but differences were not observed when testing plasma derived FIX (pdFIX) products . Potency discrepancies for both recombinant and extended half‐life (EHL) FIX products have been described between the OSA and CSA and for different OSAs related to APTT reagents…”
Section: Introductionmentioning
confidence: 99%
“…Differences between chromogenic and one‐stage FIX assays in the presence of standard half‐life recombinant FIX have been reported. Chromogenic FIX assay results were consistently around 70% of one‐stage results when two rFIX concentrates were assayed and in postinfusion samples containing one of these products (Benefix) . Furthermore, one‐stage assay results in samples containing full length recombinant FIX may be influenced by the assay reagents used in the case of Benefix and Rixubis, for which the product information states that FIX potency results can be affected by the type of APTT reagent used in the assay and that differences of up to 40% have been observed.…”
Section: Factor IX Assaysmentioning
confidence: 97%
“…It is known that using different FIX assays disparate results may be obtained in the same sample. Differences in postinfusion samples of recombinant ( r ) FIX, with CSA 30% lower than OSA FIX, have been described . The discrepancy for some extended half‐life (EHL) FIX concentrates has also been observed .…”
Section: Fix Assays For the Diagnosis Of Haemophilia Bmentioning
confidence: 97%